Management in Internalizing the Values of Ikhlas in Islamic Boarding Schools - Syahrani; Mahyuddin Barni; Ahmad Khairuddin (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The growing demand for character education has exposed a critical gap between the conceptual teaching of moral values and their authentic internalization in learners’ lived experiences, particularly within faith-based educational contexts. Despite the centrality of sincerity (ikhlas) in Islamic moral philosophy, there remains a lack of empirically validated and integrative models that systematically translate this value into consistent behavior and moral identity. This study aims to address this gap by developing and validating a structured, sequential model of sincerity internalization that integrates moral belief, moral participation, moral action, and experiential moral transformation. A mixed-methods approach within a quasi-experimental design was employed, involving 120 students from two Islamic boarding schools divided into experimental and control groups. Quantitative data were collected using a validated Sincerity Internalization Scale and analyzed through paired and independent sample t-tests with effect size calculation, while qualitative data were examined using thematic analysis to capture experiential change. The results indicate a statistically significant improvement in the experimental group (p < 0.001) with a large effect size (d = 1.21), demonstrating a substantial impact of the intervention. All dimensions of internalization improved consistently, with the experiential moral phase showing the highest transformation, indicating that sincerity becomes fully internalized when it evolves into an embodied and reflective moral identity. This study provides one of the first empirically validated sequential models of sincerity internalization that explicitly integrates experiential transformation as the culminating stage. By bridging the gap between moral cognition and lived moral practice, the findings offer a new paradigm for character education, shifting the focus from symbolic instruction to measurable and transformative moral development.